Japan Administered Account for Selected IMF Activities (JSA) : Annual Report Fiscal Year 2002. (International Monetary Fund, 2003)
This paper reports about the IMF and its activities, and particularly its technical assistance activities, the Japan Administered Account for Selected Fund Activities (JSA)-its objectives, size and scope, and use-with a focus on fiscal year 2002 and the scholarship programs. As the IMF seeks to meet its mandate, the demand on its technical assistance resources is expected to increase in a variety of areas, including helping countries to build capacity for their anti-money laundering and combating financing of terrorism (AML/CFT) efforts; to adopt and adhere to international standards and codes for financial, fiscal, and statistical management; to help Heavily Indebted Poor Countries (HIPCs) design and manage debt reduction programs; and to help low-income countries formulate and implement poverty reduction strategies. The Japan-IMF Scholarship Program for Asia supports a 12-month course of graduate studies in Japan in macroeconomics or related fields for students from Asia and the Pacific and Central Asia, and is administered by the Regional Office in Tokyo.